The Global Banking Network in the Aftermath of the Crisis : Is There Evidence of De-globalization? - Cerutti, Eugenio (IMF Working Papers; Working Paper ;, 2017)
Post-crisis dynamics show a shrinkage in the overall amount of crossborder bank lending, which has been interpreted in the literature as a retreat in financial globalization. In this paper, we argue that aggregate figures are not sufficient to support such a claim in terms of the overall structure of the global banking network. Based on a systematic approach to measuring, mapping and analyzing financial interconnectedness among countries using network theory, we show that, despite the decline in aggregate lending volumes, the structure of the network has developed increased connections in some dimensions. Some parts of the network are currently more interlinked regionally than before the crisis, and less dependent on major global lenders. In this context, at a more disaggregate level, we document the characteristics of the increasing regionalization of lending flows, the different evolution of linkages through bank affiliates and direct cross-border claims, as well as the shift in the importance of key borrower and lender nodes. These changes in the banking network have important insights in terms of policy implications since they indicate that the global banking network has evolved, but it has not undergone a generalized retrenchment in financial linkages.